2014
DOI: 10.1152/ajpregu.00163.2014
|View full text |Cite
|
Sign up to set email alerts
|

ANG II receptor subtype 1a gene knockdown in the subfornical organ prevents increased drinking behavior in bile duct-ligated rats

Abstract: Bile duct ligation (BDL) causes congestive liver failure that initiates hemodynamic changes, resulting in dilutional hyponatremia due to increased water intake and vasopressin release. This project tested the hypothesis that angiotensin signaling at the subfornical organ (SFO) augments drinking behavior in BDL rats. A genetically modified adeno-associated virus containing short hairpin RNA (shRNA) for ANG II receptor subtype 1a (AT1aR) gene was microinjected into the SFO of rats to knock down expression. Two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…ΔCt was measured by calculating the difference between the S18 and the corresponding gene of interest Ct values. For obtaining the ΔΔCt value, this value was then subtracted from the difference between the average of control S18 and control gene of interest Ct values [22,28,31,34].…”
Section: Laser Capture Microdissection and Quantitative Real-time Pcrmentioning
confidence: 99%
“…ΔCt was measured by calculating the difference between the S18 and the corresponding gene of interest Ct values. For obtaining the ΔΔCt value, this value was then subtracted from the difference between the average of control S18 and control gene of interest Ct values [22,28,31,34].…”
Section: Laser Capture Microdissection and Quantitative Real-time Pcrmentioning
confidence: 99%
“…LCM has been used by other labs to profile the molecular composition of various hypothalamic regions (Tables 1–3). For example, to highlight a few studies by way of illustration, LCM has been used to confirm: 1) the effectiveness of adeno-associated viral knockdown of angiotensin II receptor subtype 1a in the subfornical organ (SFO) of rat brain [449]; 2) reductions in gene expression in brains of steroidogenic factor 1 (SF-1) in the VMH of knock-out mice [339]; and 3) fasting-elicited changes in gene expression in the PVH and the impact of leptin replacement on these genes [440]. …”
Section: Laser-capture Microdissection Studies: Methodological Considmentioning
confidence: 99%
“…; Walch et al. ; Saxena et al. ) based on our previous study that showed ACE1 staining in the MnPO is not found in astrocytes and is mainly in neurons (Faulk et al.…”
Section: Introductionmentioning
confidence: 95%